2012
DOI: 10.1007/s00795-011-0544-5
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of ECL cells in Mastomys after long-term treatment with H2 receptor antagonist loxtidine

Abstract: Gastric ECL-cell hyperplasia and carcinoids (ECLoma) develop after 1 year in rats treated with omeprazole or 2 months in Mastomys treated with loxtidine. The aim of this study was to examine the ultrastructure of ECL cells in Mastomys after loxtidine treatment with an attempt to evaluate whether an impairment of autophagy was involved in the tumorigenesis. Mastomys were given loxtidine for 8 or 27 weeks. Morphological analysis of ECL cells showed that (1) cell size was not increased after 8 or 27 weeks; (2) se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Its export from the nucleus de-represses cell cycle progression, leading to uncontrolled proliferation and hyperplasia. It has been observed that hypergastrinemia induced by acid suppression from omeprazole or loxtidine an irreversible H2 receptor antagonist can lead to ECL cell tumors in rodents (28, 38, 39). Indeed, reports are emerging that fundic gland polyps and ECL hyperplasia do arise with prolonged PPI use, but the clinical impact remains uncertain (4042).…”
Section: Gastrin Dependence In Ecl Hyperplasiamentioning
confidence: 99%
“…Its export from the nucleus de-represses cell cycle progression, leading to uncontrolled proliferation and hyperplasia. It has been observed that hypergastrinemia induced by acid suppression from omeprazole or loxtidine an irreversible H2 receptor antagonist can lead to ECL cell tumors in rodents (28, 38, 39). Indeed, reports are emerging that fundic gland polyps and ECL hyperplasia do arise with prolonged PPI use, but the clinical impact remains uncertain (4042).…”
Section: Gastrin Dependence In Ecl Hyperplasiamentioning
confidence: 99%